ANALISIS KOINTEGRASI JUMLAH WISATAWAN, INFLASI, DAN NILAI TUKAR TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) PROVINSI BALI - JIWA ATMAJA, MADE ARISTIAWAN; N. KENCANA, I PUTU EKA; GANDHIADI, G. K. (E-Jurnal Matematika; Vol 4 No 3 (2015)DO - 10.24843/MTK.2015.v04.i03.p093, 2015)
This paper aimed to determine long-run equilibrium the tourist arrivals, inflation, exchange rate and gross domestic regional product ( GDRP ) of Bali Province used Johansen’s cointegration test. First examined whether each stationary variables using augmented dickey fuller ( ADF ) test. ADF test showed GDRP of Bali, tourist arrivals, and exchange rate are not stationary, so it is assumed stationary in first lag or I (1). While inflation is stationary in level or I (0). Johansen’s cointegration test showed the tourist arrivals, inflation, exchange rate and GDRP of Bali are not cointegrated. Notice that there is no long-run equilibrium, it can not be concluded for structural equation models.
Keywords: ADF test, tourist arrivals, exchange rate, inflation, gross domestic regional product, Johansen’s cointegration test